Empowering MSMEs clay and doll products: Navigating digital marketing challenges in the digitization era - Leny Indahsari; Heni Noviarita; Muhammad Iqbal Fasa (Universitas Muhammadiyah Magelang, 2024)
The digitization era is compelling UMKM clay and doll products in the Waru sub-district, Sidoarjo Regency, to transition from traditional to digital marketing strategies. However, they encounter challenges in digital marketing due to a lack of e-commerce knowledge. To tackle this issue, community engagement activities are conducted to enhance product marketing, expand market share, and increase income. The approach used involves training and assistance in digital marketing creation, which includes several stages such as surveys, data collection through interviews, solution formulation, and program evaluation. With the implementation of these assistance activities, UMKM clay and doll products in the Waru sub-district, Sidoarjo, can execute marketing strategies through digital platforms like Google Maps and the Shopee marketplace. This not only facilitates consumers in accessing information about UMKM products but also enriches their understanding of digital marketing.